Lying in online social networks: a bug or a feature - Maddah, Mahed; Esmaeilzadeh, Pouyan (Journal of information, communication & ethics in society (Online), 2023)
Purpose Online social networks can bridge the gap between distant individuals by simulating online experiences that closely resemble physical interactions. While people have positive experiences, such as joy, in a physical relationship and would like to enjoy those experiences online, they also have negative experiences, such as being subject to a lie. An online social network may allow users to lie to simulate a real-world social group better. However, lying must be prevented on social networks as unethical behavior. Thus, this study aims to investigate an ethical dilemma raised due to the two abovementioned perspectives. Design/methodology/approach This paper examines different aspects of lying in social networks, using a comprehensive descriptive literature review approach and a classification scheme. Findings Contrary to their initial intent, social networks are disrupting the traditional notion of human interaction, either by disregarding the presence of dishonesty or by attempting to regulate relationships. In this research, the authors examine the challenges of these two perspectives by identifying enablers, consequences and control measures of lying on social networks at the individual, social and technological levels. The authors also develop a framework to facilitate investigating this dilemma. Originality/value This paper examines a controversial topic. Although lying is unethical, allowing users to lie may be considered an appealing feature of social network platforms. This paper offers a framework to propose several research directions for future studies. This study’s examination focuses on the challenges associated with deception on social networks, prompting the formulation of three crucial questions regarding the potential impact of technology on such behavior.